Risk in the Roman world - Toner, Jerry. (Cambridge, UK ; New York, NY)
viii, 147 sayfa
Keywords: “Modern risk studies have viewed the inhabitants of the ancient world as being both dominated by fate and exposed to fewer risks, but this very readable and groundbreaking new book challenges these views. It shows that the Romans inhabited a world full of danger and also that they not only understood uncertainty but employed a variety of ways to help to affect future outcomes. The first section focuses on the range of cultural attitudes and traditional practices that served to help control risk, particularly among the non-elite population. The book also examines the increasingly sophisticated areas of expertise, such as the law, logistics and maritime loans, which served to limit uncertainty in a systematic manner. Religious expertise in the form of dream interpretation and oracles also developed new ways of dealing with the future and the implicit biases of these sources can reveal much about ancient attitudes to risk.” --